Analisis Kompensasi Dan Lingkungan Kerja Fisik Pada PT Berkarya Indonesia Sejahtera Andal - Burhanudin, Fiqri; Tumanggor, Rahmayanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study aims to analyze the compensation system and physical work environment at PT Berkarya Indonesia Sejahtera Andal. The main focus of the study was to identify how compensation and physical work environment conditions affect employee comfort, motivation, and productivity. The research method used is a qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation. The results of the study show that the compensation system in the company already refers to the structure of employee positions and responsibilities, but there is still an inequality in the perception of fairness between employees. On the other hand, the physical work environment still needs improvement, especially regarding air circulation, lighting, and workspace comfort. The conclusion of this study is that fair compensation and a supportive physical work environment have a significant effect on employee performance and job satisfaction. Therefore, it is recommended that companies conduct periodic evaluations of the compensation system and continue to improve the quality of the physical work environment to support employee productivity and welfare Keywords: Compensation, Physical Work Environment, Performance, Job Satisfaction, PT Berkarya Indonesia Sejahtera Andal